#TITLE_ALTERNATIVE# - ZAHRA (NIM : 25312007), AINI
Accumulation of aquaculture wastewater in pond that contains ammonium can disturb the metabolism of the body and cause death in freshwater prawns. Therefore, ammonium should be removed through nitrification on the suspended growth bioreactor such as batch reactor. The objective of this study was to evaluate the removal efficiencies of ammonium, to determine kinetics of biomassa growth, and to determine nitrification rate through kinetic constant and reaction order. Five laboratory scale batch reactor with working volume of each reactor 12,5 L were fed with synthetic wastewater that already contains mixed culture bacteria. This research was carried out with different amonia nitrogen concentration : 1, 2, 3, 4 and 5 mg NH3-N/l. The parameter observed during the process were temperature, pH, DO, COD, VSS, TAN, nitrite, and nitrate. The results showed that amonia nitrogen removal only happen on the first four days of operation reactor with removal efficiency ranged between 8.19% - 25.74%. Nitrite accumulation did not occur during operation reactor. In addition, from this research obtained μm was 0.038 day-1 and Ks was 0.189 mg/l. The rate of amonia nitrogen degradation follow first order reaction with reaction rate constant (k) ranged from 0.022 to 0.0748 day-1, while the rate of nitrate formation follow zero order reaction with the reaction rate constant (k) ranged from 2.9388 to 3.2977 day-1.